2015
DOI: 10.1039/c4cc08593k
|View full text |Cite
|
Sign up to set email alerts
|

Amide–triazole isosteric substitution for tuning self-assembly and incorporating new functions into soft supramolecular materials

Abstract: The proof-of-concept for the modular synthesis of new functional soft gel materials based on amide-triazole isosteric replacement has been demonstrated. A coassembly approach of isosteric amino acid-based hydrogelators was fruitfully applied for fine-tuning the release of entrapped drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
48
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 20 publications
2
48
0
1
Order By: Relevance
“…Our group has demonstrated that the isosteric substitution 29 of amides by 1,2,3-triazole groups in LMW gelators enables the adjustment of gel properties. [30][31][32] This approach have been successfully applied to different gel materials. 33,34 In general, isosteres have similar molecular shape, volume, electronic distribution, and exhibit comparable physical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Our group has demonstrated that the isosteric substitution 29 of amides by 1,2,3-triazole groups in LMW gelators enables the adjustment of gel properties. [30][31][32] This approach have been successfully applied to different gel materials. 33,34 In general, isosteres have similar molecular shape, volume, electronic distribution, and exhibit comparable physical properties.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, a one-step and convenient click-reaction has been employed to generate several new low-molecular weight organic gelators. [58][59][60][61][62][63][64] The interesting feature of this one-step reaction is that it results in the formation of new small molecules containing triazole that acts as a H-bond acceptor and a binding center for metal ions; for achieving new organogelators, we have selected 5-azido oseltamivir to implement the click-reactions on oseltamivir, anticipating the resulting conjugates as robust synthons for the development of new organic gelators with chirality, an amide linkage, a exible ester bond and a triazole ring. Furthermore, the oseltamivir moiety provides high bioactivities and biocompatibility; however, its gelation properties have never been evaluated and reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30][31][32][33][34][35] Recently, our group has demonstrated that the isosteric substitution of amides by 1,2,3-triazole groups in LMW gelators enables the modication of different gel properties. 36,37 In general, isosteres possess an almost equal molecular shape and volume, approximately the same distribution of electrons and exhibit similar physical properties. 38,39 Although this is still a recent concept in materials synthesis, 36,37,40 it has a long and successful history in medicinal chemistry for drug development.…”
Section: Introductionmentioning
confidence: 99%
“…36,37 In general, isosteres possess an almost equal molecular shape and volume, approximately the same distribution of electrons and exhibit similar physical properties. 38,39 Although this is still a recent concept in materials synthesis, 36,37,40 it has a long and successful history in medicinal chemistry for drug development. 41 In a previous and seminal work, we replaced an amide group with a 1,2,3-triazole in a glutamic acid-derived LMW gelator.…”
Section: Introductionmentioning
confidence: 99%